Deterrence by Collective Punishment May Work against Criminals but Never against Freedom Fighters - Friedel Bolle (Games, 2021)
The main goal of collective punishment (CP) is the deterrence of future “wrong-doing” by freedom fighters or terrorists, protesters against an authoritative government, polluters, students playing pranks on their teacher, football teams lacking enthusiasm, or soldiers showing cowardice to the enemy. CP could consist of the lockout of workers, additional training units for football teams, increased control of athletes and firms, up to the shooting of fellow villagers of assassins. I investigate two classes of problems. In one class, resistance against an authority is individually costly, but enough resistance can be successful (the production of a public good, for example, higher wages after a strike). In the other case, “resistance” is individually profitable (a criminal activity as pollution) and enough “resistance” produces a public bad. We find that, in the first situation, the announcement of CP never decreases the level of resistance. In the second situation, CP can be successful.